Structural delineation and computational design of SARS-CoV-2-neutralizing antibodies against Omicron subvariants - Moriyama, Saya; Anraku, Yuki; Taminishi, Shunta; Adachi, Yu; Kuroda, Daisuke; Kita, Shunsuke; Higuchi, Yusuke; Kirita, Yuhei; Kotaki, Ryutaro; Tonouchi, Keisuke; Yumoto, Kohei; Suzuki, Tateki; et al. (Nature communications, 2023)
SARS-CoV-2 Omicron subvariants have evolved to evade receptor-binding site (RBS) antibodies that exist in diverse individuals as public antibody clones. We rationally selected RBS antibodies resilient to mutations in emerging Omicron subvariants. Y489 was identified as a site of virus vulnerability and a common footprint of broadly neutralizing antibodies against the subvariants. Multiple Y489-binding antibodies were encoded by public clonotypes and additionally recognized F486, potentially accounting for the emergence of Omicron subvariants harboring the F486V mutation. However, a subclass of antibodies broadly neutralized BA.4/BA.5 variants via hydrophobic binding sites of rare clonotypes along with high mutation-resilience under escape mutation screening. A computationally designed antibody based on one of the Y489-binding antibodies, NIV-10/FD03, was able to bind XBB with any 486 mutation and neutralized XBB.1.5. The structural basis for the mutation-resilience of this Y489-binding antibody group may provide important insights into the design of therapeutics resistant to viral escape. In this study, the authors isolated SARS-CoV-2 receptor binding site monoclonal antibodies resistant to Omicron mutations. An amino acid in the receptor binding domain, tyrosine-489, is a virus-vulnerable site and a common footprint of broadly neutralizing antibodies.